Analysing the impact of being a sole or primary carer for dependent relatives on the sentencing of women in the Crown Court, England and Wales - Kane, Erica (Criminology & criminal justice, 2023)
Most quantitative sentencing research treats women and men as a homogeneous group leading to gaps in the literature regarding women’s experiences of sentencing procedures. This is problematic given the vast array of known harms that result from incarcerating women, particularly those with caring responsibilities for children. This exploratory article shares the findings from a quantitative study which considers the sentencing of women, with a particular focus on the ‘sole or primary carer for dependent relatives’ mitigation when applied to mothers. Using data from the Crown Court Sentencing Survey 2011–2015, a sample of 18,314 women defendants was derived and investigated using descriptive, bivariate and regression analysis to explore the relationship between the ‘caring’ mitigation and non-custodial sentences. The findings suggest that when the mitigation is applied to sentences of women who are carers of dependents, it does not have a strong enough relationship with non-custodial sentences. This article provides hitherto unknown statistical data and highlights the need for further research.